Biological Synthesis of Silver Nanoparticles Using Lactobacillus Probiotic Bacterium and Evaluation of Their Cytotoxicity Against Oral Squamous Cell Carcinoma Cell Line: AgNPs Cytotoxicity Against Squamous Cell Carcinoma: AgNPs Cytotoxicity Against Squamous Cell Carcinoma - Pourhaji , Mohadeese; Abbasi , Farid; Sehatpour, Aliyeh; Bakhtiari, Ronak (Galen Medical Journal, 2023)
Background: The applications of nanotechnology have greatly increased in the recent years. Nanotechnology can be used for diagnosis and treatment of many conditions in medicine and dentistry. The aim of this paper is assessment the cytotoxicity of silver nanoparticles (AGNPs) synthesized employing Lactobacillus acidophilus against human oral squamous cell carcinoma (OSCC) cell line. Materials and Methods: In this in vitro, experimental study, AgNPs were biologically synthesized by using L. acidophilus, and characterized by dynamic light scattering (DLS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), ultraviolet-visible (UV-V) spectroscopy and Fourier-transform infrared (FTIR) spectroscopy. The methyl thiazolyl tetrazolium (MTT) test was performed to assess the cytotoxic effects of AgNPs in 3.125, 6.25, 12.5, 25, 50, and 100 μg/mL concentrations within 24 hours. Results: Synthesis of AgNPs was confirmed by visual perception of dark brown color variation (from achromatic) and maximum UV-V absorption at 428 nm. TEM and SEM indicated the spherical form of AgNPs with a median size of 397 nm. FTIR spectroscopy showed the presence of functional groups from the cells involved in the reduction process. The MTT assay indicated that the biosynthesized nanoparticles made a decrease of cell livability in a concentration dependent method. Conclusion: AgNPs produced by Lactobacillus acidophilus have the potential to inhibit OSCC cell line.